Раскопки на участке у башни 6 в припортовом районе Генуэзской крепости Чембало в 2009 г. - Алексеенко, Н.А.; Дьячков, С.В. (Археологічні дослідження в Україні, 2010)
The publication is devoted to the research of defensive structures in the port area of Genovese fortress Chembalo (defensive tower 6).